Design and Fabrication of Smart Tap for Finger Protection During Hammering - Rosman, Nur Liyana Nabihah; Raja Mamat, Tengku Nur Azila; Mustafa El Bakri, Helmy; Sahak, Nurrul Hafeezah; Abdul Razak, Fadhilah (Journal of Advanced Mechanical Engineering Applications, 2025)
This study presents the design and fabrication of an innovative Smart Tap tool aimed at improving efficiency and precision in construction and woodworking activities. Although various market-ready nail holders are available, many lack ergonomic integration with the user’s grip and provide limited control to prevent nail or screw buckling during installation. The Smart Tap addresses these limitations through a user-friendly, ergonomically designed nail holder created in SolidWorks, which conforms naturally to the hand for improved ease of use and accurate placement. An impact test was conducted to evaluate the durability and performance of the holder under dynamic forces. Among three tested thicknesses, the 6 mm variant demonstrated the highest energy absorption and was selected as the optimal design. The tool was fabricated using advanced three-dimensional (3D) printing techniques, ensuring high dimensional accuracy and efficient translation from digital design to a functional product. The results confirm the Smart Tap’s effectiveness in minimizing nail buckling and enhancing operational precision, offering clear ergonomic and functional advantages over existing designs and demonstrating strong potential for broader application in hammering-related tasks.